2020
DOI: 10.3390/medicina56120651
|View full text |Cite
|
Sign up to set email alerts
|

Energy Based Vessel Sealing Devices in Thyroid Surgery: A Systematic Review to Clarify the Relationship with Recurrent Laryngeal Nerve Injuries

Abstract: Background and objectives: The principal complications associated with thyroid surgery consist in postoperative recurrent laryngeal nerve (RLN) palsy, hypoparathyroidism, intra-operative and post-operative hemorrhage. In this paper, structured as a literature review, we describe the current knowledge and the technical improvements currently employed in the field of thyroid surgery, focusing on the contribution of energy based devices in relation with the reduction of the operating time and the odds of possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…There is improvement in Gerd as assessed by the symptom questionnaires. The new onset of GERD detected on scintigraphy may not be pathological as there is a decrease in total acid production after surgery; however, it still remains an important issue and needs long-term follow-up [ [74] , [75] , [76] ].…”
Section: Discussionmentioning
confidence: 99%
“…There is improvement in Gerd as assessed by the symptom questionnaires. The new onset of GERD detected on scintigraphy may not be pathological as there is a decrease in total acid production after surgery; however, it still remains an important issue and needs long-term follow-up [ [74] , [75] , [76] ].…”
Section: Discussionmentioning
confidence: 99%
“…Today, hemostasis can be achieved in multiple ways: clamp-and-tie, electrocautery (monopoloar or bipolar), with hemostatic clips, and more advanced EBD that use thermal, ferromagnetic, or ultrasonic energy to ligate, seal and dissect tissue ( 36 ). Even though more advanced techniques with EBD have demonstrated reduced pain, wound drainage, decreased rates of neck hematoma and even hypocalcaemia ( 37 40 ), the results for EBD are inconsistent in terms of rates of RLN injury compared with conventional approaches ( 41 , 42 ). Several studies have demonstrated that traction and thermal injury are the first and second most common causes of iatrogenic RLN injury during thyroidectomy ( 39 , 43 , 44 ).…”
Section: Practice Recommendations To Minimize Dysphonia Post Thyroid ...mentioning
confidence: 99%
“…In the literature, several reports comparing the energy-based devices with the traditional technique exist. In most of these studies, Harmonic Focus and LigaSure Small Jaw (a device that works by means of advanced bipolar energy) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] were evaluated. Far fewer studies that compare the different devices with each other exist [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%